Solving vehicle assignment problems by process-network synthesis to minimize cost and environmental impact of transportation - Barany, Mate; Bertok, Botond; Kovacs, Zoltan; Friedler, Ferenc; Fan, Liang T. (My University, 2011)
A method and software are proposed for optimal assignment of vehicles to transportation tasks in terms of total cost and emission. The assignment problem is transformed into a process-network synthesis problem that can be algorithmically handled by the P-graph framework. In the proposed method, each task is given by a set of attributes to be taken account in the assignment; this is also the case for each vehicle. The overall mileage is calculated as the sum of the lengths of all the routes to be travelled during, before, after and between the tasks. (Desaulniers et al. 1998; Baita et al. 2000). Cost and emission are assigned to the mileages of each vehicle type. In addition to the the globally optimal solution of the assignment problem, the P-graph framework provides the n-best suboptimal solutions that can be ranked according to multiple criteria. The viability of the proposed method is illustrated by an example.
Keywords: P-graph; Combinatorial optimization; Vehicle assignment; Transportation